The history of psychology - Rooney, Anne (History of the humanities and social sciences., 2017)
Explores the development of psychology from its start as a branch of philosophy to current trends in the science of the mind. Includes such topics as the study of the soul, religious thought and belief, psychotherapy, altered consciousness, and how the mind was perceived in ancient times.